Introduction to the Special Issue: Select Papers Presented at the 2020 OLC Accelerate Conference and the 2021 OLC Innovate Conference - Moskal, Patsy (Online Learning, 2021)
Each year, OLJ presents a special section devoted to research shared at the Online Learning Consortium conferences. We are happy to present five research articles selected from the many presented at OLC Accelerate, held virtually November 9-18, 2020 and OLC Innovate, held virtually March 15-19, 2021. We invite the readers to consider presenting their research to OLC conferences in the future and submitting to OLJ to share their work with others in the field.